Design, manufacture and hydrodynamic evaluation of a prototype trileaflet mechanical heart valve for aortic valve replacement - Wium, Elsmari (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.